Spatio-temporal evolution of the resilience of Chinese border cities - Lili Sui; Lili Sui; Fei Peng; Fei Peng; Siyu Wu; Siyu Wu (Frontiers Media S.A., 2022)
In China, border cities are developing in the direction of trade, investment, tourism, and regional diversification and becoming crucial for the national opening-up strategy and inter-regional exchange. In this study, we construct a comprehensive system for measuring and evaluating the resilience of border cities in China that also reveals the spatial and temporal characteristics of resilience. Three representative sample zones (Northeast, Northwest, and Southwest) are selected within the three major regions of China to analyze the regional differences in border city resilience and propose targeted coping strategies. The findings of this study are as follows. First, the spatial distribution of resilience in Chinese border cities varies significantly, with the overall resilience decreasing in the following order: Northeast China > Southwest China > Northwest China > North China > Tibetan China. Higher resilience of border cities is predominantly related to better economic foundations and advantages in border trade. Second, the resilience of China's border cities has increased significantly over the past decade, with highly resilient border cities concentrated in the northeastern part of China, the northern part of Xinjiang, and Guangxi Province. Moreover, high resilience generally spreads to surrounding low-resilience cities over time. Third, the spatial distribution and development trends of resilience levels differ among the three sample zones. Therefore, it is crucial to improve urban resilience according to the regional characteristics of each border city and its specific developmental stage.